Species Composition of Mycobacteria Isolated from Exotic Animals - Zavgorodnii, A.I.; Pozmohova, S.A.; Paliy, A.P.; Sviridova, K.O.; Pavlichenko, O.V.; Ganova, L.O.; Palii, N.V.; Kovalenko, L.V.; Boiko, V.M.; Pidgorskiy, V.S.; Завгородній, А.І.; Позмохова, С.А.; et al. (PH "Akademperiodyka" of the NAS of Ukraine, 2026)
Nontuberculous or atypical mycobacteria represent a large group of saprophytic and potentially pathogenic bacteria that can cause mycobacteriosis in humans and animals. Tuberculous mycobacteria most commonly infect mammals, while atypical mycobacteria have a much wider host range, including mammals, fish, amphibians, reptiles, and birds. Some species of nontuberculous mycobacteria are the etiologic factor in the occurrence of anthropozoonoses. Animals transmit these diseases, and human infection occurs through direct contact with the carrier or through its biological waste. Currently, there is little information available in Ukraine on the spread of infections associated with atypical mycobacteria in animals kept as pets. The study aimed to investigate the species composition of mycobacteria that can potentially cause mycobacteriosis in exotic companion animals. The research was conducted from 2023 to 2025 at the Laboratory for the Study of Tuberculosis of the National Scientific Center “Institute of Experimental and Clinical Veterinary Medicine” (Kharkiv). Methods. A bacteriological method was used to examine 463 samples, including droppings from companion birds, cloaca swabs from five red-eared turtles, feces from an African hedgehog, and samples of internal organs from an ornamental duck and peacock. These samples belonged to 39 different species of animals. Results. Out of the 463 samples, 84.7% tested positive for mycobacteria. Of those, 1.4% were M. scrofulaceum, 1.9% were M. avium, and 96.7% were M. genavense. Additionally, a photochromogenic culture of M. kansasii was isolated from a parrot for the first time in Ukraine. Cryptosporidium (20.5%), non-acid-fast bacteria (83.5%), molds and yeast-like fungi (42.2%), and Cryptococcus (2.0%) were found in 76% of fecal samples. Microorganism cultures of M. avium and Nocardia sp. were isolated from ornamental ducks. Conclusions. The results of the study indicate that exotic birds, especially parrots, are most susceptible to M. genavense. Due to the danger posed by opportunistic mycobacterial species to exotic animal owners, routine examinations of exotic animals for mycobacteriosis are necessary, as is compliance with sanitary and hygienic requirements for their maintenance.